Contribution of PPi-Hydrolyzing Function of Vacuolar H+-Pyrophosphatase in Vegetative Growth of Arabidopsis: Evidenced by Expression of Uncoupling Mutated Enzymes - Asaoka, Mariko; Segami, Shoji; Ferjani, Ali; Maeshima, Masayoshi (Frontiers in Plant Science, 2016)
The vacuolar-type H+-pyrophosphatase (H+-PPase) catalyzes a coupled reaction of pyrophosphate (PPi) hydrolysis and active proton translocation across the tonoplast. Overexpression of H+-PPase improves growth in various plant species, and loss-of-function mutants (fugu5s) of H+-PPase in Arabidopsis thaliana have post-germinative developmental defects. Here, to further clarify the physiological significance of this important enzyme, we newly generated three varieties of H+-PPase overexpressing lines with different levels of activity that we analyzed together with the loss-of-function mutant fugu5-3. The H+-PPase overexpressors exhibited enhanced activity of H+-PPase during vegetative growth, but no change in the activity of vacuolar H+-ATPase. Overexpressors with high enzymatic activity grew more vigorously with fresh weight increased by more than 24 and 44%, compared to the wild type and fugu5-3, respectively. Consistently, the overexpressors had larger rosette leaves and nearly 30% more cells in leaves than the wild type. When uncoupling mutated variants of H+-PPase, that could hydrolyze PPi but could not translocate protons, were introduced into the fugu5-3 mutant background, shoot growth defects recovered to the same levels as when a normal H+-PPase was introduced. Taken together, our findings clearly demonstrate that additional expression of H+-PPase improves plant growth by increasing cell number, predominantly as a consequence of the PPi-hydrolyzing activity of the enzyme.